2012
DOI: 10.1002/biof.1055
|View full text |Cite
|
Sign up to set email alerts
|

Aging modifies the enzymatic activities involved in 2‐arachidonoylglycerol metabolism

Abstract: One of the principal monoacylglycerol (MAG) species in animal tissues is 2-arachidonoylglycerol (2-AG), and the diacylglycerol lipase (DAGL) pathway is the most important 2-AG biosynthetic pathway proposed to date. Lysophosphatidate phosphatase (LPAase) activity is part of another 2-AG-forming pathway in which monoacylglycerol lipase (MAGL) is the major degrading enzyme. The purpose of this study was to analyze the manner in which DAGL, LPAase, and MAGL enzymes are modified in the central nervous system (CNS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Therefore, specific increase in 2-AG levels observed in middle-age Ts65Dn mice could be related to the associated Alzheimer's disease-like neuropathology. Alternatively, the relative increase in older Ts65Dn mice may be secondary to age-dependent changes, since alterations in the expression and activity of endocannabinoid metabolic enzymes and particularly, in MAGL and DAGLα, have been described in aged rodents (Pascual et al, 2013;Piyanova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specific increase in 2-AG levels observed in middle-age Ts65Dn mice could be related to the associated Alzheimer's disease-like neuropathology. Alternatively, the relative increase in older Ts65Dn mice may be secondary to age-dependent changes, since alterations in the expression and activity of endocannabinoid metabolic enzymes and particularly, in MAGL and DAGLα, have been described in aged rodents (Pascual et al, 2013;Piyanova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation may involve aging‐related increases in endocannabinoid/CB1R tone in regions of the brain associated with appetite regulation, such as the nucleus accumbens (Maldonado‐Irizarry et al ., 1995; Winters et al ., 2012). Indeed, these changes may be brought about by increased CB1R expression, or in response to the altered activity of enzymes implicated in the synthesis and/or degradation of endocannabinoids (Pascual et al ., 2013). Consequently, such a scenario may convey the apparent augmentation of rimonabant's anorectic response in older mice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in our understanding of metabolic regulation by the ECS, as well as previous reports of age‐related deregulation of cannabinoid receptors and endocannabinoid hydrolysing enzymes (Pascual et al ., 2013, 2014), little is known regarding the involvement of this signalling system in aging‐associated metabolic dysfunction. Herein, we explored the effects of chronic (14 day) administration of rimonabant (SR141716), a potent and selective CB1R inverse agonist (Landsman et al ., 1997), on the energy budgets of young (4 month old) and aged (17 month old) adult male mice.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the activity of these enzymes in the regulation of anandamide and 2-AG contents is critical. In this regard, Pascual et al ., (2014) demonstrated that FAAH activity was decreased in the frontal cortex from patients with Alzheimer's disease [ 139 ] whereas the similar findings were reported for MAGL in Alzheimer's disease experimental murine models [ 140 - 142 ]. In line with this data, Piyanova et al ., (2015) found an elevated MAGL activity during aging [ 143 ].…”
Section: Does the Endocannabinoid System Modulate Sleep Disorders In mentioning
confidence: 77%